RESERVATION PLICIES FOR WEAKER SECTION ENACTED BY THE GOVERNEMNT IN CONTEXT OF JUDICIARY - Bansal, Arpana (International Journal of Psychosocial Rehabilitation, 2010)
The judges in India have fortunately a most potent judicial power in their hands, namely, the power of judicial review1. In democratic countries, the judiciary is given a place of great significance. The primary function of the courts is to settle disputes and dispense justice between one citizen and another, but courts also resolve disputes between one citizen and the state and the various organs of the state itself. In many countries with written constitution, there prevails the doctrine of judicial review. It means that the constitution is the supreme law of the land and any law inconsistent there with is void. In this way the judiciary function not only to interpret constitution, but also uphold constitution. So, it has power of judicial review. The courts act as the protector and guardian of the supremacy of the constitution by keeping all authorities legislative, executive, administrative, judicial, or quasi-within legal bounds.